"I've Got the Energy to Change, But I Haven't Got the Energy for This Kinda Therapy": A Qualitative Analysis of the Motivations Behind Democratic Therapeutic Community Drop-Out for Men With Sexual Convictions. (September 2022) - Duncan, Katie; Winder, Belinda; Blagden, Nicholas; Norman, Christine
Prison-based democratic therapeutic communities (TCs) provide an alternative to mainstream prison, where prisoners can work on psychological difficulties and address offending behavior. Research demonstrates TCs are effective at reducing reoffending rates for residents who stay in therapy 18+ months, and those who drop out of TCs offend at a significantly higher rate than those who complete therapy. Thus, it is important to reduce attrition in TCs. No research has yet explored the explanations for TC drop out offered by those with sexual convictions. The present study uses Interpretive Phenomenological Analysis to qualitatively explore the accounts of men with sexual convictions ( n = 7) who dropped out of a TC in a UK prison. Results highlight that issues surrounding external responsivity, therapeutic relationships, and treatment readiness were salient in the participants' accounts of drop out. This research has implications for TCs seeking to better understand and address attrition of people with sexual convictions.